Evaluating Government Policy Implementation at Junior High School in Surabaya: Language Attitude Perspective - Zahra Nirwani, Nimas Ageng (Language Horizon: Journal of Language Studies, 2024)
The Surabaya City Government has implemented an English language familiarization policy as an effort to improve students’ language skills in facing global challenges. In recent years, English has become key in international communication, global information access, and competition in the job market. English occupies a central position in the current era, becoming a global communication tool that enables cross-cultural interaction and collaboration. According to Crystal (2003), a language achieves true global status when it develops a special role that is recognized in every country. The aim of this research was to find out students’ attitudes towards learning English at school and to look for factors that influence language attitudes. This research adopts Gardner and Lambert’s (1985) theory about language attitudes combined with Ostrom’s (1994) theory. This research takes a qualitative approach. This research collects data from three classes at SMPN 38 Surabaya. The results of the research show that the majority of students show a positive attitude towards the new English language familiarization policy at school. Students are also aware of the importance of English in this era. Several social factors also influence language attitudes, such as peer pressure and teacher support. Keywords: Language attitude, Government policy, Social influences, English usage